Performance analysis for indoor optical wireless communication system / Norshahida Abdul Wahab - Abdul Wahab, Norshahida (2010)
The worldwide demand for wireless communications is being met in many places by installed single-mode fiber networks. However, there is still a significant "first-mile" problem, which seriously limits the availability of broadband Internet access. Optical wireless communication (OWC) or free-space optical wireless communications (FSO) has emerged as a viable technology for bridging gaps in existing high-data rate communications networks, and as a temporary backbone for rapidly deployable mobile wireless communication infrastructure. This paper will review the link performance of the indoor optical wireless system. The optical wireless link was modeled and simulated using a commercial optical system simulator named OptSim by RSoft.